A Case of Essential Thrombocythemia and IgA Nephropathy with Literature Review of the Concurrence. (2nd September 2019) - Rahimian, Shoja; Johnson, Timothy; Herb, Ronald
Abstract : Myeloproliferative neoplasms such as essential thrombocythemia (ET) have been associated with glomerular disease on rare instances. A case of ET associated with immunoglobulin A nephropathy (IgAN) is described in a 57-year-old man with a history of hypertension. Progressively worsening renal function was noted in the patient along with unexplained mild thrombocytosis. Pathological review of renal biopsy identified IgAN concurrently with newly diagnosed JAK2-mutated ET. The patient was started on aspirin therapy and closely monitored for his renal function. A literature review of the association of ET and renal disease revealed nine cases of ET associated with IgAN, focal segmental glomerulosclerosis, and fibrillary glomerulonephritis. Comparison of the pathological features of the renal biopsies within the cases noted mesangial proliferation as a common finding, which has been described to be potentiated by platelet-derived growth factor (PDGF). This commonality may represent a link between ET and glomerular disease which deserves further attention in future cases. Improved management of such cases depends on the recognition of the combined occurrence of ET and glomerular diseases and uncovering the shared pathogenesis between platelets and glomeruli.